Investigation of forecasted risk interrelationship: base on GARCH model, causality in China markets - Lin, Shu-Shian (Journal of Business Economics and Management, 2014)
This paper used data from the Shenzhen and Shanghai stock markets to simulate the adjusted volatility, and applied time series methods to realize the relationships of the volatilities between the two markets. The unit root test, and co-integration analysis to show whether it exists equilibrium relationship. The result showed that it presented the co-integrated vectors between the volatilities of Shanghai and Shenzhen Stock Exchanges during the research period, and it made the regression more meaningful. Finally, it also showed that the volatility exerted one way influence between these two markets. It significantly rejected for a null hypothesis of Shanghai stock market does not granger caused Shenzhen stock market, and the results of simulated volatilities were consistent with the results in reality.